2015
DOI: 10.1098/rspb.2014.2555
|View full text |Cite
|
Sign up to set email alerts
|

Ventrolateral and dorsomedial frontal cortex lesions impair mnemonic context retrieval

Abstract: The prefrontal cortex appears to contribute to the mnemonic retrieval of the context within which stimuli are experienced, but only under certain conditions that remain to be clarified. Patients with lesions to the frontal cortex, the temporal lobe and neurologically intact individuals were tested for context memory retrieval when verbal stimuli (words) had been experienced across multiple (unstable context condition) or unique (stable context condition) contexts; basic recognition memory of these words-in-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…It should also be pointed out that this dorsomedial frontal region was coactivated with the ventrolateral prefrontal region in our previous functional neuroimaging studies of active memory retrieval (9,26). We have recently provided evidence in a behavioral-lesion study in the human brain that the dorsomedial frontal region is indeed involved in memory retrieval (10). In a visual-verbal paradigm it was shown that, whereas the ventrolateral prefrontal cortex is specifically involved in the isolation of particular information from a previously encoded event, the dorsomedial frontal region is more generally involved in memory retrieval.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…It should also be pointed out that this dorsomedial frontal region was coactivated with the ventrolateral prefrontal region in our previous functional neuroimaging studies of active memory retrieval (9,26). We have recently provided evidence in a behavioral-lesion study in the human brain that the dorsomedial frontal region is indeed involved in memory retrieval (10). In a visual-verbal paradigm it was shown that, whereas the ventrolateral prefrontal cortex is specifically involved in the isolation of particular information from a previously encoded event, the dorsomedial frontal region is more generally involved in memory retrieval.…”
Section: Discussionmentioning
confidence: 97%
“…This impairment was not accompanied by general memory loss of the type observed after limbic medial temporal lobe lesions (11)(12)(13). Patients with ventrolateral prefrontal lesions performed as well as normal control subjects on recognition memory of the presented stimuli, but were impaired when they were asked to retrieve selectively specific aspects of the memorized information in a task in which words and their context entered into multiple relations with each other across trials and, therefore, retrieval could not be supported by simple recognition memory (10). Taken together, these results suggest that the midventrolateral prefrontal cortex plays a critical role in the top-down modulation of activity for the retrieval of specific features of mnemonic information when simple familiarity and/or unambiguous stimulus-to-stimulus relations are not sufficient for memory retrieval.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…This is because they should react adaptively and flexibly to a coo expression, with multiple meanings, depending on the situation. In human, the vlPFC is reported to be involved in working memory of nonspatial content (Nee et al, 2013), and is also engaged in retrieval of mnemonic context especially in multiple contexts (Chapados and Petrides, 2015). Therefore, the vlPFC might spend a great deal of time processing ambiguous information in social communication, and try to make an accurate decision against multiple possibilities based on memory.…”
Section: Processing Of Facial Expressions In the Vlpfcmentioning
confidence: 99%
“…This finding is consistent with the hypothesis that area 45 is critical for controlled memory retrieval 8,34,35 . There is functional neuroimaging evidence of the involvement of area 45 in the controlled effortful mnemonic retrieval of verbal information, such as the free recall of words that appear within particular contexts 9 and a more recent study has shown that patients with lesions to the ventrolateral prefrontal region, but not those with lesions involving the dorsolateral prefrontal region, show impairments in the active controlled retrieval of the contexts within which words were presented 43 . The above findings regarding the differential involvement of the two cytoarchitectonic areas that comprise Broca’s region are consistent with the hypothesis that the prefrontal granular component, i.e.…”
Section: Discussionmentioning
confidence: 99%